Analisis Bibliometrik : Tren Penelitian Asesmen Computer Based Test Pada Tahun 2015-2025 - Azka, Dea Alvionita; Alrefi, Alrefi; Dewi, Ratna Sari; Patriot, Evelina Astra (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
The aims of this research is to find out and review the research trends of computer-based test assessment in education science over the past 10 years. The research method used is a literature study using bibliometric analysis method. Bibliometric analysis is a quantitative method used to measure and analyze scientific publications, such as journal articles, books, or conference proceedings and metadata processing. As for the metadata used in this research was sourced from Google Scholar. Database search and analysis used Publish or Perish (PoP) and VOSviewer software. The results showed that there was trends in research on increasing interest in adaptive question development, integration of CBT with LMS, and the effect of CBT on student learning outcomes. This research can be used as a reference for further research on variables that have not shown correlation through Vosviewer. Some recommendations related to this research include the importance of expanding the use of database sources to collect published articles, for example through the WOS (Web of Science) database. The implication of this research is the availability of literature as preliminary analysis results to be used in further research